Right on the spot - Laudanna, Carlo; Alon, Ronen (Thrombosis and Haemostasis, 2006)
The arrest of rolling leukocytes on various target vascular beds is crucial for their recruitment at inflammatory sites and secondary lymphoid tissues. Leukocyte arrest is predominantly mediated by integrins interacting with either constitutive or inducible endothelial ligands. Integrins are cytoskeletally regulated heterodimers maintained in largely low affinity conformational states on circulating leukocytes. For arrest to occur, the affinity of integrin heterodimers must be enhanced in situ upon leukocyte encounter with proper endothelial-displayed chemokines or chemoattractants which bind and signal through specific G-protein coupled receptors (GPCRs) on the leukocyte surface. Recent studies suggest that this integrin activation involves rapid conformational alterations locally induced at confined leukocyte-endothelial contact sites. Following binding, integrin microclustering reinforced by associations with the cortical actin cytoskeleton further enhances integrin-mediated adhesiveness under shear stress. These events are controlled by complex signaling events, involving a series of small GTPases, as well as protein and lipid kinases which are triggered by chemokine bound GPCRs. To rapidly mediate this specialized function, subsets of signaling proteins and their specific targets are thought to preexist in pre-assembled multi-molecular complexes or signalosomes. Recent in vitro dissection of chemokine-triggered integrin activation on lymphocytes and neutrophils suggests that these signalosomes may vary both in composition and mode of activity between different immune cell types and distinct integrins. We review in this article recent findings on key elements implicated in chemokine triggering of integrin activation on rolling leukocytes, and discuss the possible existence of preformed proadhesive signaling networks in different subsets of leukocytes.
Keywords: Integrins; chemokines; selectins; leukocytes; signal transduction; inflammation